Assessment of staffing needs for physicians and nurses at Upazila health complexes in Bangladesh using WHO workload indicators of staffing need (WISN) method - Joarder, Taufique; Bente Kamal Tune, Samiun Nazrin; Nuruzzaman, Md; Alam, Sabina; de Oliveira Cruz, Valeria; Zapata, Tomas (BMJ Journals, 2022)
This article was published in The BMJ Open [ © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2019-035183 The Journal's website is at: https://bmjopen.bmj.com/content/10/2/e035183